2006
DOI: 10.1111/j.1365-2419.2005.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Spawning habitat and daily egg production of sardine (Sardina pilchardus) in the eastern Mediterranean

Abstract: Spawning habitats of two eastern Mediterranean sardine, Sardina pilchardus (Walbaum, 1792), stocks (coastal waters of central Aegean and Ionian Seas) are characterized from daily egg production method (DEPM) surveys conducted during the peak of the spawning period. The latter occurs earlier in the Aegean Sea (December) than in the less-productive Ionian Sea (February). Single-parameter quotient analysis showed that the preferred bottom depth for spawning was 40-90 m in both areas but sardine selected sites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 16 publications
12
31
0
Order By: Relevance
“…Patterns of larval fish distribution originate from complex spatial and temporal interrelationships that are strongly affected by the seasonality and duration of their meroplanktonic existence (Olivar et al 1998;Koutrakis et al 2004;Palomera et al 2005). Several studies have focused on how biological processes such as high food concentrations, low predator stocks, and certain hydrographic features regulate the distribution and abundance of planktonic organisms, including fish larvae Somarakis et al 2000Somarakis et al , 2006, even if biological-physical interactions are considered to be more important than purely biological forcing mechanisms (Cuttitta et al 2004;Sabates 2004). It has been shown that coastal environments often constitute favourable habitats for the early life stages of fishes living in different marine ecosystems (McGowen 1993), representing nursery areas for species exhibiting distinct spawning habits (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of larval fish distribution originate from complex spatial and temporal interrelationships that are strongly affected by the seasonality and duration of their meroplanktonic existence (Olivar et al 1998;Koutrakis et al 2004;Palomera et al 2005). Several studies have focused on how biological processes such as high food concentrations, low predator stocks, and certain hydrographic features regulate the distribution and abundance of planktonic organisms, including fish larvae Somarakis et al 2000Somarakis et al , 2006, even if biological-physical interactions are considered to be more important than purely biological forcing mechanisms (Cuttitta et al 2004;Sabates 2004). It has been shown that coastal environments often constitute favourable habitats for the early life stages of fishes living in different marine ecosystems (McGowen 1993), representing nursery areas for species exhibiting distinct spawning habits (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The collected data of bacterial group relative abundances and environmental parameters such as chl a concentration, temperature, and salinity were used to estimate the 'preferred' range of environmental parameters for each bacterial group using a quotientrule analysis (QRA, Somarakis et al 2006). Each envi ronmental variable was divided into regular intervals for which the frequencies of occurrence were calculated and expressed in percentages.…”
Section: Analysis Of Bacterial Group Distributionmentioning
confidence: 99%
“…It is no surprise then that peak spawning activity of small pelagic clupeid fish, such as pilchard (Sardinops sagax) and anchovy (Engraulis australis), generally occurs when offshore transport is low and larval food concentrations are high (Somarakis et al 2006;Muhling et al 2008a). These fish species, as well as sandy sprat (Hyperlophus vittatus), blue sprat (Spratelloides robustus) and garfish (Hyporhamphus melanochir), comprise the majority of the diet of the penguins from Penguin Island (Klomp and Wooller 1988a;Wienecke 1989;Wooller et al 1991;Connard 1995;Bradley et al 1997;Murray et al 2011).…”
Section: Introductionmentioning
confidence: 99%